Potential Benefits from Innovations to Reduce Heat and Water Stress in Agriculture - Hendricks, Nathan P. (My University, 2017)
A key challenge in determining the optimal research and development (R&D) investment portfolio for adapting to climate change in agriculture is to understand the potential benefits from reducing alternative sources of climate damages. Existing econometric studies are not able to separately identify the impacts of heat and water stress because higher temperatures cause damages through both mechanisms. To resolve the identification problem, I introduce measures of water deficit and water surplus into a regression analysis that estimates the nonlinear impacts of heat and water stress on nonirrigated rental rates in the central United States. The results indicate rental rate losses of 33% ($9.5 billion annually) by mid-century due to climate change in scenario RCP 4.5. I find that 65% of the projected damages are due to heat stress, 32% due to increasing water deficit, and 3% due to increasing water surplus. However, the source of damages varies spatially.
Citation: Nathan P. Hendricks, "Potential Benefits from Innovations to Reduce Heat and Water Stress in Agriculture," Journal of the Association of Environmental and Resource Economists 5, no. 3 (July 2018): 545-576. https://doi.org/10.1086/697305
Keywords: Climate change; Agriculture; Ricardian analysis; JEL: Q16; JEL: Q54; JEL: Q55